Assessment of the comparative ability of accounting bases in predicting future cash flows: Evidence from Nigeria - Orits Frank Ebiaghan (Trends Economics and Management, 2018)
Purpose of the article: This study examines the comparative abilities of accrual-based and cash-based accounting information to predict future operating cash flows with particular focus on quoted Nigerian non-financial companies. Secondary data were utilized for the study and were extracted from published annual statements and accounts of eighty (80) quoted firms in Nigeria between 2005-2015. Methodology/methods: Data collected were statistically analysed with the aid of the Ordinary Least Square (OLS) regression method, correlation analysis, variance inflation factor (VIF) tests for multicollinearity, and the Breusch-Pagan/Cook Weisberg test for heteroscedasticity. 5% level of the test of significance was employed to measure the degree of statistical relationship between stated variables. Scientific aim: This research is aimed at empirically ascertaining, by means of available statistics, the comparative predictive abilities of accrual-based and cash-based accounting information in forecasting future cash flows for quoted non-financial companies in the Nigerian stock exchange. Findings: It has been revealed in this study that historical earnings data prepared under the accrual-basis possessed superior predictive ability over operating cash flows data in forecasting future cash flows of quoted non-financial firms in Nigeria. Conclusions: Company management who are saddled with the responsibility of preparation and presentation of financial statements as part of their management responsibility should, as a matter of utmost priority, uphold integrity and transparency by adhering strictly to the provisions of accounting standards so as to enhance reliability and decision-usefulness of financial disclosures with a view to improving the predictive ability of accounting information.
Keywords: M40; M41; M49; 650; Accounting Bases; accounting information; accrual accounting; cash accounting; cash-flows predictions